50 contemporary artists you should know - Finger, Brad; Weidemann, Christiane (Munich : Prestel, 2018)
This survey of great contemporary artists is the perfect introduction to the exciting world of art today. Artists working after World War II faced a confounding array of challenges, as stylistic barriers were broken, technology advanced, and issues of sexuality and race came to the forefront.
Gerhard Richter -- David Hockney -- Bruce Nauman -- Anselm Kiefer -- Barbara Kruger -- Paul McCarthy -- Jeff Wall -- Marina Abramovic -- Richard Prince -- Jenny Holzer -- Bill Viola -- Mona Hatoum -- Marlene Dumas -- Nan Goldin -- Sophie Calle -- Cindy Sherman -- Anish Kapoor -- Robert Gober -- Mike Kelley -- Andreas Gursky -- Jeff Koons -- William Kentridge -- Shirin Neshat -- Raymond Pettibon -- Ai Weiwei -- Peter Doig -- Maurizio Cattelan -- Neo Rauch -- Tracey Moffatt -- Takashi Murakami -- Gabriel Orozco -- Pipilotti Rist -- Rachel Whiteread -- Tracey Emin -- Damien Hirst -- Zhang Huan -- Elizabeth Peyton -- Jake & Dinos Chapman -- Olafur Eliasson -- Matthew Barney -- Sam Taylor-Wood -- Mariko Mori -- Tal R -- Wolfgang Tillmans -- Chris Ofili -- Doug Aitken -- Gregor Schneider -- Kara Walker -- Jonathan Meese -- Anselm Reyle.
Original edition published in 2007.
Includes index.
Keywords: Artet boterore; Arti vizual; 1900-2099 -- Arti modern; Artists -- Biography-biografia -- Artiste boterore; Art, Modern -- 20th century-shekulli 20-te; Art, Modern -- 21st century-shekulli i 21-te; Art, Modern; Artists; Arti vizual-piktura-skulptura-instalacione-dizajni-fotografia-arti bashkekohor; Biography